Can herb-clover mixes compensate for the lack of milk in the diet of early-weaned lambs?. Issue 2 (2nd April 2020) - Corner-Thomas, Rene A.; Cranston, Lydia M.; Kemp, Peter D.; Morris, Steve T.; Kenyon, Paul R.
ABSTRACT: This experiment investigated the feasibility of using herb-clover mixes to enable early weaning of lambs at ∼60 days of age. Over two years, twin lambs weighing more than 16 kg were allocated to three treatments: ryegrass pastures until 90 days-of-age, herb-clover mix until 90 days-of-age or weaned at ∼60 days of age onto herb-clover mix. In 2014, lambs offered the herb-clover mix, weaned at 60 or 90 days, were heavier at 90 days than lambs grazing on pasture with their dams. In 2015, lambs that weaned early onto the herb-clover mix were lighter at the same age as lambs that remained with their dam, but they still achieved a commercial weight. Ewes weaned early were heavier at weaning than ewes suckling lambs on ryegrass pasture in both years. Under some conditions, early weaning of lambs onto a herb-clover mix can be an effective alternative to conventional weaning on ryegrass pasture.